A mini literature review on sustainable management of poultry abattoir wastes - Ozdemir, Saim; Yetilmezsoy, Kaan (SPRINGER, 2020)
Poultry slaughtering and post-processing activities generate different kinds of highly perishable organic wastes and by-products. Poultry carcass yields are typically about 70-75% of the live bird weight, the rest is accepted as inedible waste. Depending on the efficiency of the processing methods birds' blood, feather, head, feet, offal and inedible viscera, and in some cases, treated solids make up the slaughterhouse solids in the poultry industry. The management of nutritive organic waste should aim to produce value-added by-products such as pet animal or aquaculture feed components, energy through thermochemical or biochemical processes, and agricultural fertilizer. Conventional rendering at specified temperatures and pressures are widespread processing and well-established methods to produce sellable products in the form of protein-rich meals such as poultry powder, feather powder, and fat. The utilization of raw or processed poultry by-products for animal feed is become strictly banned in both national and international scales for the poultry industry. There has been increasing stress to find alternative areas demanding nutrient-rich solid by-products. The objective of this study is to review several studies with a special focus on poultry abattoir-related activities to draw attention to proper management practices from the environmental point of view. The review shows that best management of the process, high-quality wastes need further innovative and effective processing methods to find possible feed additive either for fish or other animal meal, as well as alternative waste treatment process that provides an opportunity for energy recovery and high-quality bio-nutrient source to be used for crop production.
Keywords: Poultry abattoir waste; Characterization; Sustainable management; Value-added products; ANAEROBIC CO-DIGESTION; SLAUGHTERHOUSE WASTE; FISH-MEAL; PROTEIN-SOURCE; WATER; FEED; MANURE; REPLACEMENT; PERFORMANCE; PRODUCTS; Environmental Sciences & Ecology